The role of vitamin and microelement supplementation in the treatment of ethanol-induced liver disease - Artur W. Uździcki; Aleksandra Zych; Barbara Świerad; Marta Wawrzynowicz-Syczewska (Gastroenterology Review)
High alcohol intake leads to an inadequate diet and impaired absorption, transport, and utilization of nutrients in the body, which results in malnutrition. Micronutrient supplementation, such as vitamins A, E, group B vitamins, folic acid zinc, and selenium may have a positive effect on those patients. In this article, the actual supplementation recommendations for vitamins and microelements in ethanol-induced liver disease patients are presented.